Comparative efficacy of fixed-dose combinations of long-acting muscarinic antagonists and long-acting β2-agonists: a systematic review and network meta-analysis. (April 2016) - Schlueter, Max; Gonzalez-Rojas, N; Baldwin, Michael; Groenke, Lars; Voss, Florian; Reason, Tim
Background: A number of long-acting muscarinic antagonist (LAMA)/long-acting β2-agonist (LABA) fixed-dose combinations (FDCs) for treatment of moderate-to-very severe chronic obstructive pulmonary disease (COPD) have recently become available, but none have been directly compared in head-to-head randomized controlled trials (RCTs). The purpose of this study was to assess the relative clinical benefit of all currently available LAMA/LABA FDCs using a Bayesian network meta-analysis (NMA). Methods: A systematic literature review identified RCTs investigating the efficacy, safety and quality of life associated with licensed LAMA/LABA FDCs for the treatment of moderate-to-very severe COPD. RCTs were screened for inclusion in the NMA using prespecified eligibility criteria. Data were extracted for outcomes of interest, including change in trough forced expiratory volume in 1 second (tFEV1 ) from baseline, St. George Respiratory Questionnaire (SGRQ) percentage of responders, Transition Dyspnea Index (TDI) percentage of responders, change in SGRQ score from baseline, change in TDI focal score from baseline, moderate-to-severe exacerbations, all-cause discontinuation, and discontinuation due to adverse events. Results: Following screening, a total of 27 trials from 26 publications with 30, 361 subjects were eligible for inclusion in the NMA. Nonsignificant results were seen in most analyses comparing efficacy, exacerbations and discontinuation rates of included LAMA/LABA FDCs (i.e. aclidinium/formoterol 400/12 µg, glycopyrronium/indacaterol 110/50 µg, tiotropium + olodaterol 5/5 µg, umeclidinium/vilanterol 62.5/25 µg). Meta-regression controlling for post-bronchodilator percentage of tFEV1 predicted at baseline as well as meta-regression adjusting for concomitant use of inhaled corticosteroids at baseline was performed to assess the magnitude of effect modification and produced similar results as observed in the base case analysis. Conclusion: All LAMA/LABA FDCs were found to have similar efficacy and safety. Definitive assessment of the relative efficacy of different treatments can only be performed through direct comparison in head-to-head RCTs. In the absence of such data, this indirect comparison may be of value in clinical and health economic decision-making.